Bonhoeffer : pastor, martyr, prophet, spy - Metaxas, Eric (Nelson Books, an imprint of Thomas Nelson, 2020)
As Adolf Hitler and the Nazis seduced a nation, bullied a continent, and attempted to exterminate the Jews of Europe, a small number of dissidents and saboteurs worked to dismantle the Third Reich from the inside. One of these was Dietrich Bonhoeffer, a pastor and author. In his blockbuster New York Times bestselling biography, Eric Metaxas takes both strands of Bonhoeffer's life--the theologian and the spy--and draws them together to tell a searing story of incredible moral courage in the face of monstrous evil. Metaxas presents the fullest accounting of Bonhoeffer's heart-wrenching decision to leave the safe haven of America to return to Hitler's Germany, and sheds new light on Bonhoeffer's involvement in the famous Valkyrie plot and in "Operation 7," the effort to smuggle Jews into neutral Switzerland. In a deeply moving narrative, Metaxas uses previously unavailable documents including personal letters, detailed journal entries, and firsthand personal accounts to reveal dimensions of Bonhoeffer's life and theology never before seen